PENGARUH PERUBAHAN TEMPERATUR DAN KOMPOSISI TERHADAP TEKSTUR DAGING ANALOG YANG DIHASILKAN MENGGUNAKAN TEKNIK EKSTRUSI - Giovan Ganandy; Herianto Herianto (Jurnal Rekayasa Mesin, 2022)
Analogue meat products currently available are plant-based meats which have a texture and taste like conventional meats. The commonly used ingredient is soy protein. The purpose of this study is to see the interaction of the parameters of the percentage of soybean flour Isolated Soy Protein (ISP) and wheat flour Wheat Flour (WF), water content parameters, barrel temperature parameters, and oil content parameters on the texture of the analog meat. The extrusion process is carried out by a twin screw extrusion machine operates at speed of 50 rpm. The material is then fed into the extruder machine through the hopper. The specimen to be tested is in the form of a cylinder with a diameter of 10mm and a length of 50mm. Texture analysis test was carried out using the Brookfield CT3 Texture Analyzer machine. test results were analyzed using Analysis of Variance (ANOVA) and Turkey test. The barrel temperature parameter has the most influence on the Hardness, Adhesiveness, Gumminess and Chewiness values, while the water content parameter has the most influence on the Cohesiveness value, and the oil content has the most influence on Springiness. The interaction between the parameters of barrel temperature and water content (temperature*water) has a significant effect on Hardness, Gumminess and Chewiness (Turkey's test, p<0.05). Meanwhile, the interaction of the parameters of water content and oil content (water*oil) did not show a significant effect (Turkey's test, p<0.05) on the results of the texture analysis test. Meanwhile, the interaction of oil*temperature parameters showed a significant effect (Turkey's test, p<0.05) on Gumminess and Chewiness.